Prominent Midlatitude Circulation Signature in High Asia's Surface Climate During Monsoon. Issue 23 (11th December 2017) - Mölg, Thomas; Maussion, Fabien; Collier, Emily; Chiang, John C. H.; Scherer, Dieter
Abstract: High Asia has experienced strong environmental changes in recent decades, as evident in records of glaciers, lakes, tree rings, and vegetation. The multiscale understanding of the climatic drivers, however, is still incomplete. In particular, few systematic assessments have evaluated to what degree, if at all, the midlatitude westerly circulation modifies local surface climates in the reach of the Indian Summer Monsoon. This paper shows that a southward shift of the upper‐tropospheric westerlies contributes significantly to climate variability in the core monsoon season (July–September) by two prominent dipole patterns at the surface: cooling in the west of High Asia contrasts with warming in the east, while moist anomalies in the east and northwest occur with drying along the southwestern margins. Circulation anomalies help to understand the dipoles and coincide with shifts in both the westerly wave train and the South Asian High, which imprint on air mass advection and local energy budgets. The relation of the variabilities to a well‐established index of midlatitude climate dynamics allows future research on climate proxies to include a fresh hypothesis for the interpretation of environmental changes. Key Points: An established large‐scale index of westerly waves helps to reveal significant anomalies in High Asia's local and regional surface climate These anomalies appear as widespread, distinct dipole patterns in surface‐air temperature and moisture Midlatitude climate dynamics can be incorporated for explaining surface‐climate variability in monsoonal High Asia